KELAYAKAN BUBUK SINGKONG KUNING SEBAGAI MASKER UNTUK PERAWATAN KULIT WAJAH BERMINYAK - Sri Rahmadani; Prima Minerva (Jurnal Tata Rias dan Kecantikan, 2022)
Traditional yellow cassava mask can be used as a cosmetic facial treatment made from natural and easy to get and contains vitamins that are good for facial skin. The purpose of this study is 1) To analyze how to make yellow cassava mask feasibility yellow cassava mask traditionally for oily facial skin care, 2) To analyze the feasibility of yellow cassava mask seen from the content of vitamin  B1, C, and Ca contained in yellow cassava mask, 3) To analyze the feasibility of yellow cassava mask seen from the texture, aroma, adhesions, and favorite of panelists. This type of research is descriptive quantitative research. The object of this study was yellow cassava which was made into a natural powder mask. This type of data uses primary data. Data collection techniques using documentation, observation, and tests. Data analysis techniques used are descriptive analysis techniques and analysis methods.The result of the study is the quality of traditional mask yellow cassava powder based on laboratory test results can be known that Vitamin B1 contained in the traditional mask of yellow cassava powder is as much as 0.03 mg. Vitamin C contained in the traditional mask of yellow cassava powder as much as 70.19 mg. Ca contained in traditional mask yellow cassava powder as much as 24,957%. Based on organoleptic tests showed the texture, aroma, adhesion, and liking of panelists had a fairly high level of assessment. Some panelists said that the traditional mask of yellow cassava powder is very good as a mask that can overcome oil content on oily facial skin, as well as make the face smoother and brighter. It is recommended to students to add insights in the field of traditional cosmetics and use them in accordance with the condition of the facial skin